PENGARUH KOMPETENSI TERHADAP KINERJA PEGAWAI PADA DINAS SOSIAL KABUPATEN BURU SELATAN - LAURENS, SAMSONS (Fakultas Ilmu Sosial dan Ilmu Politik, 2019)
This study aimed to analyze the effect of competence on the performance of employees at South Buru District Social Service. This research uses explanatory research with survey data collection methods. The study lasted for 2 months, ie from January to the month of February 2017 in South Buru District Social Service. The sampling technique in this research is a probability sampling technique saturated sample (full sample) that as many as 39 people. Data were analyzed using multiple linear regression. The results showed that the competence on the basis of the characteristics of the suitability of the knowledge, skills and self-concept has a significant influence on the performance of employees in the South Buru District Social Service, with variable suitability of knowledge as the dominant variable.